MARKET ANALYSIS FACTORS - O. A. Zemlyanskiy (Вестник университета)
Different markets have many differences, their own characteristics and specifics, but the essence and characteristics of the market, as a set of objects, subjects, their structure and conditions of interaction, the subject of entrepreneurial activity in the market allow us to highlight general provisions, to form factors that make possible to analyse any markets on which a certain type of objects are created, used, distributed and redistributed in the process of interaction of market entities with the emergence and functioning of the structure, principles, rules and other legislative and legal support. The author proposes unified factors, which is the basis of possible to determine the state, analyses and compares a wide variety of markets to identify opportunities, conditions and prospects for the presence of various companies and types of business, opportunities and efficiency of entrepreneurial activities.